2020
DOI: 10.1177/2158244020968085
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions, Financial Development, Trade, and Income in North America: A Spatial Panel Data Approach

Abstract: The current study attempts to explore the determinants of CO2 emissions per capita considering spatial effects for a panel of 21 North American countries. The results corroborate the existence of spatial dependence in per capita carbon dioxide emissions and its determinants. Adverse environmental spillover effects are found for all hypothesized determinants while per capita income showed a positive impact. Furthermore, the existence of environmental Kuznets curve hypothesis is proven with a turning point of 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 75 publications
1
20
1
2
Order By: Relevance
“…This study also demonstrates that there is a monotonically heightening (positive) association between FD and CO 2 . This result is in line with previous results of [ 69 ] for 21 North American economies and [ 61 ] who analyze an extensive panel of more than 100 countries. These authors show the positive impact of financial development on CO 2 emissions, and that this effect is reduced when including institutional factors into the analysis.…”
Section: Resultssupporting
confidence: 93%
“…This study also demonstrates that there is a monotonically heightening (positive) association between FD and CO 2 . This result is in line with previous results of [ 69 ] for 21 North American economies and [ 61 ] who analyze an extensive panel of more than 100 countries. These authors show the positive impact of financial development on CO 2 emissions, and that this effect is reduced when including institutional factors into the analysis.…”
Section: Resultssupporting
confidence: 93%
“…Janjua et al [16] reported that foreign direct investment (FDI) and the industry sector were responsible for pollution. On the other hand, the literature found a mix of the negative and statistically insignificant effects of FDI on CO 2 emissions [17,18]. Khan et al [19] found that fossil fuels reduced and renewable energy improved the environmental quality in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the factors that contribute to air pollution reduction has been a hot topic in academia. So far, the main influencing factors include the level of economic development (Lin et al, 2014;Xie al, 2016;Jin et al, 2017;Ahmed et al, 2021), environmental regulation Wang and Li, 2021;, industrial structure (Pei et al, 2021;Xue et al, 2021), transport infrastructure (Kinney et al, 2011;Lozhkin et al, 2020;Liu and Dong, 2021), technological progress (Chen et al, 2019;Wu et al, 2020;Ma et al, 2022), financial development (Yang et al, 2021;Yang et al, 2022) and financial capacity (Kuai et al, 2019;Mahmood, 2020;Yang et al, 2022;Yin et al, 2022). Among these factors technological progress is an important means of air pollution abatement, most previous studies have focused on the impact of technological progress on air pollution abatement (Wang et al, 2019;Dong et al, 2020;Amann et al, 2020;Jahanger et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The cities were divided into resource-based and nonresource-based cities according to the National Sustainable Development Plan for Resource-based Cities (2013-2020 issued by the State Council to examine the differential effects of examining Environmentally biased technological advances on air pollution. The results are shown in Table 10.…”
Section: Heterogeneity Of Whether It Is a Resource-based Citymentioning
confidence: 99%